(untitled) (Rivista Italiana di Filosofia Analitica Junior, 2014)
In the recent debate about the nature of properties, dispositional essentialism, which claims that a property possesses its powers essentially, seems to provide an interesting alternative to the quite simple and problematic view that properties are to be identified through primitive qualities, quidditates (this position may be called quidditism). However, it is not easy to characterize explicitly and uncontroversially dispositional essentialism, in particular when it comes to the treatment of powers. A further reference to primitive qualities may prove to be unavoidable, thus suggesting a medium between quidditism and dispositional essentialism. Whatever means are used in the explanation of a property’s nature, the resort to a rock-bottom entity like a quidditas seems to be the only way to avoid a regress.